2013
DOI: 10.1007/s13762-013-0352-7
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variations in the risk of adverse birth outcomes in Spain

Abstract: The objective of this study was to describe the spatial risk-patterns of prematurity and low birth weight in Spain. A descriptive spatial analysis of births registered in the Spanish Vital Statistics during 2004-2008 using municipalities as the observation unit was carried out. Besag-York-Mollié autoregressive spatial models were adjusted using the Integrated Nested Laplace approximation to calculate relative risks and posterior probabilities of having very and moderate preterm or low weight newborns. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As spatial analysis has been a good way to carry out epidemiological studies by mapping various problems such as prematurity, Bloch 20 used a spatial approach through the census in Philadelphia to study the geographic pattern of premature births to black mothers born abroad and in the United States, and systematic variation across communities was observed in race, poverty, and crime. Another study carried out by Castelló et al 21 , in Spain, also showed spatial variations in the risk of prematurity and low birth weight, highlighting some areas with high risk that could be related to industry or agriculture, in addition to other factors, such as vulnerability unequal social status.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…As spatial analysis has been a good way to carry out epidemiological studies by mapping various problems such as prematurity, Bloch 20 used a spatial approach through the census in Philadelphia to study the geographic pattern of premature births to black mothers born abroad and in the United States, and systematic variation across communities was observed in race, poverty, and crime. Another study carried out by Castelló et al 21 , in Spain, also showed spatial variations in the risk of prematurity and low birth weight, highlighting some areas with high risk that could be related to industry or agriculture, in addition to other factors, such as vulnerability unequal social status.…”
Section: Discussionmentioning
confidence: 84%
“…Among the studies where geoprocessing was used, the analyses on the profile of births 14 , morbidity 7 , 15 , and neonatal, post-neonatal (28 to 364 days of life) or infant mortality (under 1 year of life) 6 stand out 16 , 17 . Specifically, studies were found on the spatial distribution of premature births in Brazil 7 , 18 , 19 and in other countries 20 , 21 , 22 , 23 , whose risk areas were identified and spatial associations with some factors were studied, such as those related to health 7 , industry 21 , agriculture 22 , the environment 23 or some socioeconomic conditions 19 .…”
Section: Introductionmentioning
confidence: 99%